2021
DOI: 10.1177/10776990211048883
|View full text |Cite
|
Sign up to set email alerts
|

Ontologies of Journalism in the Global South

Abstract: For many years, scholars have accepted the pedagogic, practical, and theoretical universalization of journalism standards. Benchmarks on what journalists, teachers, or researchers should do in their day-to-day activities were set in the West. While a small group of scholars questioned or openly challenged this philosophy, many acquiesced. However, the era of sustained Western discourse dominance seems over if unremitting calls for re-theorization are anything to go by (Glück, 2018;Mitchelstein & Boczkowski, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 56 publications
0
16
0
2
Order By: Relevance
“…Finally, it is necessary to highlight that JMCQ has recently welcomed debates and research concerned with de-westernizing journalism and media studies (see Mutsvairo et al, 2021). These matters are twofold to interrogate the validity and the relevance of western subjects of study, theories, methodologies, and arguments in non-western contexts, and to bring attention to analytical frameworks, research topics, and findings beyond a handful of countries and academic cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is necessary to highlight that JMCQ has recently welcomed debates and research concerned with de-westernizing journalism and media studies (see Mutsvairo et al, 2021). These matters are twofold to interrogate the validity and the relevance of western subjects of study, theories, methodologies, and arguments in non-western contexts, and to bring attention to analytical frameworks, research topics, and findings beyond a handful of countries and academic cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Adherence to Western publication norms and English-language dominance, along with an interest in studying in Western institutions, can inadvertently reinforce Global North intellectual dominance (Das, 2017;Glück, 2018;Keim, 2014). For instance, Ganter and Ortega (2019) and Mutsvairo et al (2021) found that Latin American researchers are more inclined to publish in English using Western frameworks rather than indigenous approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This special issue aims to broaden the understanding of the role and influence of peripheral actors in journalism. In plugging this extant research gap, the special issue also seeks to dispel widespread generalizations in which Anglo-American conceptions of "peripheral actors in journalism" are "applied with an underlying assumption of universality that neglects the specificities of the contexts in which they were conceived" (Mutsvairo et al 2021(Mutsvairo et al , 1001. While there are undeniable global similarities, as we have already noted, it is equally true that the "emerging" and established journalistic practices are also "coloured by local factors across the globe" which result in practices that challenge Anglo-American conceptions "that generalise what are, in fact, diverse and complex [peripheral] newsmaking cultures" (Mabweazara 2018).…”
Section: Centrepiece Of "Peripheral" Studiesmentioning
confidence: 99%
“…This special issue, first, acknowledges that the transformation of journalism where news is increasingly detached from journalism, albeit coloured by local factors (Steensen and Westlund 2020), is a global phenomenon. It submits that the transformation of journalism is broadly seen as striking at the very heart of the ontology of journalism (Mutsvairo et al 2021)-the obsession with the disruption and rapture of the very nature of journalism-particularly in terms of how we have traditionally understood it as a stable and normatively distinct profession with a clearly defined "professional identity and ideology" (Deuze 2005), orchestrated and policed by "mainstream journalists" as the sole arbiters. We consider the aforementioned conception of the transformation of journalism as limiting.…”
Section: Introductionmentioning
confidence: 99%